Impact of Dentine Pretreatment with Matrix Metalloproteinase Inhibitors on Bond Strength of Coronal Composite Restorations: A Systematic Review and Meta-analysis of In Vitro Studies - Jamal, Hasan; Yaghmoor, Rayan; Abed, Hassan; Young, Anne; Ashley, Paul (European Journal of Dentistry, 2022)
Matrix metalloproteinase (MMP) enzymes participate in collagen matrix degradation, including in dentine, potentially compromising bond strength. Therefore, MMP inhibitors have been hypothesized to improve restoration bond strength and stability. This systematic review aimed to evaluate the influence of different MMP inhibitors applied as dentine surface pretreatments on the immediate (24 hours) and longer term (months) bond strength of direct coronal composite restorations. This systematic literature review followed the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) statement. A systematic literature search of three databases (Ovid MEDLINE, Ovid Embase, and Google Scholar) was conducted independently by two reviewers from inception to April 2022. An adapted quality assessment tool was independently applied by two reviewers for risk of bias assessment. RevMan v5.4 software was used for meta-analyses. A randomeffectsmodel was used to generatemean differences with 95% confidence intervals for treatment and control comparisons. The Q-test and I2-test were used to test for heterogeneity. The proportion of total variance across studies attributable to heterogeneity rather than chance was calculated. Overall effects were tested using the Z-test, while subgroup differences were tested using Chi-squared tests. Of 934 studies, 64 studies were included in the systematic review and 42 in the meta-analysis. Thirty-one MMP inhibitors were reported, three of which were included in the meta-analysis: 2% chlorhexidine (CHX), 0.3M carbodiimide (EDC), and 0.1% riboflavin (RIBO). Pretreatment with 2% CHX for 30 and 60 seconds did not significantly improve bond strength compared with controls either immediately or after long-termageing. However, pretreatment with 0.3MEDC and 0.1% RIBO (but not CHX) significantly improved bond strength compared with control groups both immediately and over time. Most studies showed a medium risk of bias. These in vitro findings pave the way for rationale clinical trialing of dentine surface pretreatment with MMP inhibitors to improve clinical outcomes.
Keywords: restorations; bond strength; matrix metalloproteinase inhibitors; enzymes; caries; dentine.